Effect of load alterations on the effective regurgitant orifice area in chronic aortic regurgitation. Issue 4 (1st October 2002) - Kim, Y J; Jones, M; Shiota, T; Tsujino, H; Qin, J X; Bauer, F; Sitges, M; Kwan, J; Cardon, L A; Zetts, A D; Thomas, J D
Abstract : Objective: To evaluate the load dependence of effective regurgitant orifice area (ROA) in an animal model of chronic aortic regurgitation. Methods: Eight sheep were studied 10–20 weeks after the surgical creation of aortic regurgitation. After baseline studies, 500 ml of blood, angiotensin II, and nitroprusside were infused sequentially. Electromagnetic flow meters were used as reference standards to determine aortic regurgitation volume. The time–velocity integral was acquired using the continuous wave Doppler method. Results: Baseline aortic regurgitant volume varied from 8 ml (regurgitant fraction 28%) to 29 ml (59%), with a mean (SD) value of 17 (8) ml; mean ROA was 0.15 (0.05) cm 2 . During angiotensin II infusion, aortic regurgitation volume (20 (8) ml) and mean diastolic aortoventricular pressure gradient (62 (18) mm Hg) increased by 26 (16)% and 48 (64)%, respectively (p < 0.01 for both). ROA did not change (0.16 (0.06) cm 2, p = 0.15). During nitroprusside infusion, aortic regurgitant volume (13 (7) ml, p = 0.05) and diastolic pressure gradient (25 (13) mm Hg, p < 0.05) decreased. ROA did not change (0.15 (0.05) cm 2 ). When analysing 32 stages together, aortic regurgitant volume ( r = 0.78, p < 0.01) and regurgitant fraction ( r = 0.55, p < 0.01) correlated well with ROA. However, diastolic pressure gradient ( r = 0.28) was not significantly correlated with ROA. Conclusions: In an animal model of chronic aortic regurgitation, ROA did not change with load alterations.